Streshantering van die psigiatriese verpleegkundestudent: Deel II - S. M. Nieuwoudt; M. Greeff; M. Poggenpoel (AOSIS, 1993)
Stress is caused by the demands of everyday life and is an integral part of our lives. The manner in which stress is coped with, remains the responsibility of the individual herself. To be in the nursing profession today, is highly demanding. The psychiatric nurse experiences more stressors, because she is involved in a specialised area, where she uses herself as a therapeutic instrument on a scientific basis. The psychiatric nursing student finds herself in a situation where she is confronted by stressors from her personal and professional environment, as well as stressors caused by her present training in psychiatric nursing. To ensure quality nursing and job satisfaction by the psychiatric nursing students, it is important that their stressors must be identified and that they must learn in good time ways how to effectively cope with it. The psychiatric nursing student must learn ways to cope with her own stressors and consequently she will be in a position to be assistance to her patients. Coping with stress unsuccessfully and not identifying a high stress load, can have disastrous consequences for both the psychiatric nursing student as well as for the specific organisation in which she is involved. The purpose of this research is to identify the precise stressors which influence the psychiatric nursing student during her training, as well as to establish guidelines to direct the psychiatric nursing student where coping with stress is concerned.